Post-imparting Brønsted acidity into an amino-functionalized MOF as a bifunctional luminescent turn-ON sensor for the detection of aluminum ions and lysine. Issue 36 (4th September 2019) - Liu, Yanhong; Huangfu, Mengjie; Wu, Pengyan; Jiang, Min; Zhao, Xiaoli; Liang, Lili; Xie, Liheng; Bai, Jianguo; Wang, Jian
Abstract : A MOF with amino and Brønsted acid sites, exhibiting bifunctional luminescent turn-on sensing properties for the detection of Al3+and Lys. Abstract : A novel aldehyde- and amino-functionalized luminescent metal–organic framework, Cd–TCHO, was constructed through the solvothermal reaction of 4, 4′, 4′′-tricarboxytriphenylamine, 2-amino-3-pyridinecarboxaldehyde and cadmium nitrate and was characterized. Post-synthetically oxidizing the aldehyde groups into carboxylate groups afforded a new complex, Cd–TCOOH, and this successful conversion process was confirmed by FT-IR and 1 H NMR studies. With the Brønsted acidic sites inside the cavities of Cd–TCOOH, it could be used as a luminescent sensor for Al 3+ detection with a high selectivity and sensitivity (LOD = 0.54 ppb), which could be attributed to the coordination between free Brønsted acidic sites and Al 3+ . Importantly, it could also detect Lys among 20 kinds of natural amino acids; the selectivity, sensitivity and the sensing mechanism are discussed in detail. Also, both of the sensing processes were carried out in the HEPES buffer.